2020
DOI: 10.1097/pai.0000000000000854
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Secretory Phospholipase A2 Group IIa in Breast Cancer and Correlation to Prognosis in a Cohort of Advanced Breast Cancer Patients

Abstract: Secreted phospholipase A2 group IIa (sPLA2-IIa) has been shown to promote tumor genesis and cell proliferation. The properties of this group of enzymes are utilized in liposomal drug delivery of chemotherapy. sPLA2-IIa is also under investigation as a possible treatment target in itself, and as a prognostic marker. The expression of sPLA2-IIa in breast cancer has not been examined extensively, and never using immunohistochemistry. We sought to investigate the expression of sPLA2-IIa in a cohort of advanced bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Only a few studies exist determining the expression of Group IIA sPLA 2 in breast cancer [ 37 , 39 , 40 ]. Those studies that do exist measuring Group IIA sPLA 2 protein expression in clinical tissues report similar levels in both primary and metastatic tumors [ 37 ]. We validated that this type of expression was also seen in the cell line panel tested ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies exist determining the expression of Group IIA sPLA 2 in breast cancer [ 37 , 39 , 40 ]. Those studies that do exist measuring Group IIA sPLA 2 protein expression in clinical tissues report similar levels in both primary and metastatic tumors [ 37 ]. We validated that this type of expression was also seen in the cell line panel tested ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…This prospect is exciting as we have previously shown that SPRL containing doxorubicin, a standard treatment for breast cancer, demonstrated improved efficacy over SSL in xenograft models of prostate cancer [ 35 ]. Besides, a recent study assessing the expression of Group IIA PLA 2 in a cohort of advanced breast cancer patients reported a large proportion to have high levels of expression in both primary tumors and metastasis [ 37 ]. Thus, this study tested the hypothesis that SPRL-IPA-3 displays an enhanced ability to inhibit breast cancer cell growth and induce cell death as compared to free IPA-3 or IPA-3 encapsulated in SSL.…”
Section: Introductionmentioning
confidence: 99%
“…Similar SPLA2 gene and protein imbalances that affect crucial metabolic pathways have already been detected in lung and gynecological carcinomas including breast and ovarian cancer. Interestingly, aberrant SPLA2 protein expression affects epithelial to mesenchymal transition in these cacners (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipases are a diverse group of enzymes with over 30 isoforms all involved in the cleaving of phospholipids [ 343 ] and are divided into several classes depending on their catalytic mechanism, evolutionary relationships, structure, and localization (whether extracellular or intracellular). Of these isoforms, secretory phospholipase A 2 (sPLA 2 ) has been associated with several inflammatory pathologies and atherosclerosis, as well as promoting the tumor proliferation of prostate, pancreatic, and breast cancers [ [344] , [345] , [346] ]. sPLA 2 is also known to have a strong preference for cleaving negatively charged phospholipid head groups such as phosphatidylserine [ 347 ] and lipid bilayers over free lipids making it an excellent candidate as a target for liposomal drug delivery.…”
Section: Targeted Nanoliposomes For Breast Cancer Treatmentmentioning
confidence: 99%